A Dual Channel OTA with Adaptive Reference Control Module and Current Mirror for Biomedical Applications - Ernest Ravindran R. S, Sudhakiran Gunda, Pampana Mitra Sai, Munagala Bindu Madhavi, Kilamsetty Praneeth, S Vamsee Krishna (Design Engineering, 2021)
The Wearable and implantable ECG (electrocardiography) monitors, such as cardiac rhythm and heart failure, are commonly used to monitor individual’s heart condition for early detection of cardiovascular diseases. In terms of power, noise and linearity, an ECG sensor is one of the most critical elements. A low noise and low power feedback amplifier based on a current-reused Operational Transconductance Amplifier (OTA) and current mirror OTA that meets the stringent requirements of ECG recordings is present in the existing system. In the proposed system, design of OTA for ECG sensors is digitalized through threshold converters and current mirror OTA the various references is fetched to extract the unique points. A dual channel OTA is implemented here with an adaptive reference control module and current mirror appraoch. The proposed architecture is designed and simulated by using the Xilinx Modelsim (method 1) and Tanner tool (method 2). The proposed architectures focus on reduced power consumption and size of the circuit.